Determination of fluorine in copper concentrate via CaF molecules using laser-induced breakdown spectroscopy. Issue 8 (19th July 2021) - Tang, Zhiyang; Zhou, Ran; Liu, Ke; Hao, Zhongqi; Liu, Kun; Zhang, Wen; Li, Qingzhou; Zhu, Chenwei; Li, Xiangyou
Abstract : CaF molecular emission as an alternative to F atomic emission was proposed to detect the fluorine element in copper concentrate. Abstract : Copper concentrate is the main raw material for smelting copper, but some harmful elements will accelerate the damage of the smelting equipment and affect the ecological environment, and the fluorine element is one of them. The aim of the present work is to develop a method for the determination of fluorine in copper concentrate using laser-induced breakdown spectroscopy (LIBS). In this work, the CaF molecular band is proposed to replace fluorine atomic lines as the analysis target to detect the fluorine element. The calibration curves between the fluorine content and intensity of CaF molecules in copper concentrate samples (ZBK338B and ZBK340A) were established using the standard addition method, and the values of determination coefficient R 2 are above 0.99; the predicted relative error (RE) of fluorine in samples ZBK338B and ZBK340A was 4.13% and 4.93%, and the calculated limits of detection (LoDs) were 0.0033 wt% and 0.0052 wt% for samples ZBK338B and ZBK340A, respectively, which could meet the actual application requirements for fluorine determination in copper concentrate. This work demonstrated the feasibility of LIBS to realize reliable fluorine determination in the copper smelting industry.